ANALISIS MAKNA ASOSIATIF DALAM LIRIK LAGU BERSENDA GURAU KARYA RAIM LAODE : KAJIAN SEMANTIK - Aannisah Nadya Shafwah; Alda Khafifah Ritonga; Melinda Issa Bella Br. Tarigan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the associative meanings contained in the lyrics of RaimLaode's song "Bersenda Gurau." The associative meanings examined include connotative, stylistic,and affective meanings. The research method used was qualitative with a descriptive approachthrough listening and note-taking techniques. The research data, in the form of words, phrases,and sentences containing associative meanings, were then analyzed and presented in tables anddescriptions. The results indicate that the song's lyrics utilize connotative meanings to conveysymbols and figurative messages, stylistic meanings to build an aesthetic atmosphere, and affectivemeanings to express affection, empathy, and emotional support. These findings indicate that thelyrics of "Bersenda Gurau" not only convey a direct message but also construct an emotional andaesthetic atmosphere, in accordance with semantic theory and associative meaning. This researchcontributes to understanding the depth of poetic language and emotional expression incontemporary Indonesian song lyrics.